If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -4 = (x + -5) Reorder the terms: -4 + y = (x + -5) Reorder the terms: -4 + y = (-5 + x) Remove parenthesis around (-5 + x) -4 + y = -5 + x Solving -4 + y = -5 + x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + y = -5 + 4 + x Combine like terms: -4 + 4 = 0 0 + y = -5 + 4 + x y = -5 + 4 + x Combine like terms: -5 + 4 = -1 y = -1 + x Simplifying y = -1 + x
| -78=-6x+3(x-16) | | (X-2)-(3x+4)=2 | | x-1.1=3.2 | | 2(X-1)+4x-3=13 | | 2y/3=6-8 | | 2y/3=(6-8) | | 8t-6t=1-5 | | 3x^4-4x^3+1=0 | | 2(x+6)+3x=-3 | | 2x+3y+(x-12)+(y+20)=360 | | 2(3a+2)=13 | | y^2-13y+15=0 | | 200-w=106 | | 7(y)+9(y)=96 | | 89=-w+167 | | 60h^5=48h^7 | | (x+8)(x+18)=0 | | X^2+2=2.6 | | 6x+24=13x-50 | | 5+(x-9)=26+(x-10) | | 6x^2-75x-225=0 | | 7x-10=x+11 | | 16=88+n | | 3y-12x=-48 | | 4x-10=7x-14 | | 9x-(5x+6)+10=2x | | a*b=121 | | axb=121 | | 82=21+m | | 9x-9=3x+10 | | 125*x=116.8224299 | | X^2+19x+40=0 |